In Defence of Environmental Anthropocentrism - Zlatica Plašienková; Eva Smolková (Studia Ecologiae et Bioethicae)
The critique of anthropocentrism has accompanied environmental thinking since its inception. However, we lack a deeper analysis of anthropocentrism and its forms. The authors of this study concentrate on analysing selected forms of anthropocentrism that were prominent in different periods of the history of European culture. They offer a basic typology of anthropocentrism and characterize philosophical, religious, philosophical-theological and philosophical-scientific anthropocentrism. They also include a fifth form of anthropocentrism, which they call environmental anthropocentrism. The authors consider changes that are important from a philosophical, ethical and axiological perspective and analyse the potential of anthropocentrism in comparison with some of environmental anthropocentrism its alternative forms, such as biocentrism and cosmocentrism. They also attempt to assess the significance of environmental anthropocentrism and the potential for its implementation in human-environmental relations. The environmental anthropocentrism proposed here is a potential solution with applicability to the search for a moderate, humble, non-arrogant, respectful and responsible human approach to relations with nature.